ANALISIS KESULITAN BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN PADA MANUSIA DI KELAS VIII MTs NEGERI 1 PONTIANAK - Sari, Tika; Afandi, Afandi; Tenriawaru, Andi Besse (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The study serves to analyze the percentage of learning difficulties, the level of study difficulties, and the factors that lead to class VIII C MTsN 1 Pontianak in human digestive material. This kind of research is quantitative with the shape of case studies. This study sample was a student VIII C of the year 2020/2021. The research instruments used are diagnostic tests that function to identify students who have learning difficulties, questionnaires, and interviews to discern the underlying factors behind learning difficulties. Studies show a percentage of students learning difficulties in human digestive material 61.87% with difficulties category. The level of learning difficulties consists (level I) of 26,67% small learning difficulties (level II) of 33.33%, and heavy difficulties (level III) of 40,00%. The causes of student learning difficulties caused internal factors (43.78%) with sufficient category, and learning difficulties caused external factors (53.67%) with sufficient category